The lipid A region of lipopolysaccharides from Rhizobiaceae activates bone marrow granulocytes from lipopolysaccharide-hyporesponsive C3H/HeJ and C57BL/10ScCr mice - Pedron, T (Blackwell Science Inc, 2000)
We established in previous studies that the binding of Salmonella lipopolysaccharide (LPS) to constitutive receptors of low affinity triggers the expression of the inducible LPS-binding molecule CD14 in bone marrow cells (BMC) of C3H/HeOU mice, but not in BMC from C3H/HeJ mice. We show in this study that BMC from C3H/HeJ and C57BL/10ScCr mice do not express CD14 after exposure to LPSs from Salmonella enterica and Bordetella pertussis, but do express this marker when treated with several LPSs from Rhizobiaceae, or their lipid A fragments. This shows that the constitutive LPS receptor in BMC from C3H/HeJ and C57BL/10ScCr mice is fully able to trigger a complete signalling cascade. Results of cross-inhibition of the binding of radiolabelled LPS indicated that active LPSs (from R. species Sin-1 and R. galegae) and inactive LPSs (from S. enterica and B. pertussis) bind to the same site of the constitutive LPS receptor of C3H/HeJ cells. Furthermore, binding of R. species Sin-1 LPS, and signalling induced by this LPS, were both inhibited by pre-exposure of C3H/HeJ cells to B. pertussis lipid A. This correlation between binding and signalling suggests that in C3H/HeJ cells, the constitutive receptor, which recognizes a large panel of LPSs from different origins, appears selectively unable to be activated by some particular LPSs, such as those of Enterobacteria and Bordetella.